A Photosensitizer Lanthanide Nanoparticle Formulation that Induces Singlet Oxygen with Direct Light Excitation, But Not By Photon or X‐ray Energy Transfer. (25th July 2017) - Chouikrat, Rima; Baros, Francis; André, Jean‐Claude; Vanderesse, Régis; Viana, Bruno; Bulin, Anne‐Laure; Dujardin, Christophe; Arnoux, Philippe; Verelst, Marc; Frochot, Céline
Abstract: We report the design and synthesis of europium‐doped gadolinium oxysulfide nanoscintillators Gd2 O2 S:Eu 3+ conjugated with two different photosensitizers (PSs): a zinc chlorin (ZnTPC) and a zinc phtalocyanine (ZnPc) by covalent bonding through a layer of N ‐(3‐trimethoxysilylpropyl)diethylenetriamine (TPDA). These conjugates were designed to be activated under X‐ray excitation to allow a photodynamic effect, although this desired outcome was not achieved in this study. The monodispersed nanoparticles of ∼70 nm diameter were pegylated to be stabilized in aqueous suspension. It was shown that the PSs conserved their photophysical properties once conjugated to the nanoscintillator and efficient singlet oxygen was obtained upon photo‐irradiation. However, no energy transfer was observed from the nanoscintillator to the photosensitizer neither under photo‐ nor X‐ray irradiation. Abstract : We report the design and synthesis of europium‐doped gadolinium oxysulfide nanoscintillators Gd2 O2 S:Eu 3+ conjugated with two different photosensitizers (PS) by covalent bonding through a layer of N ‐(3‐trimethoxysilylpropyl)diethylenetriamine (TPDA). PEG was added. These conjugates were designed to be activated under X‐ray excitation to allow a photodynamic effect, although this desired outcome was not achieved in this study. It was shown that the PSs conserved their photophysical properties once conjugated to the nanoscintillator and efficient singlet oxygen was obtained upon photo‐irradiation. However, no energy transfer was observed from the nanoscintillator to the photosensitizer neither under photo‐ nor X‐ray irradiation.